Contact dermatitis due to transdermal therapeutic systems: a clinical update - Paolo, Romita (Acta Biomed, 2019)
Transdermal therapeutic systems (TTS) have become a popular method of drug delivery because they allow drugs to be delivered in a rate-controlled manner, avoiding first-pass metabolism and the fluctuating plasma concentrations encountered with oral medications. Unfortunately, TTS may provoke adverse skin reactions as irritating contact dermatitis and allergic contact dermatitis: TTS seem to be ideally suited to produce sensitization because they cause occlusion, irritation, due to the repeated placement of the allergen in the same skin location. Since TTS consist of an adhesive, an active pharmaceutical drug and enhancing agents, sensitization may develop owing to one of these three agents. The purpose of this manuscript is to review known responsible allergens of contact dermatitis due to TTS. (www.actabiomedica.it)